Advances in Materials Processing Proceedings of Chinese Materials Conference 2017 - Han, Yafang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This proceedings volume gathers selected papers presented at the Chinese Materials Conference 2017 (CMC2017), held in Yinchuan City, Ningxia, China, on July 06-12, 2017. This book covers a wide range of material surface science, advanced preparation and processing technologies of materials, high purity materials, silicon purification technology, solidification science and technology, performance and structure safety of petroleum tubular goods and equipment materials, materials genomes, materials simulation, computation and design. The Chinese Materials Conference (CMC) is the most important serial conference of the Chinese Materials Research Society (C-MRS) and has been held each year since the early 1990s. The 2017 installment included 37 Symposia covering four fields: Advances in energy and environmental materials; High performance structural materials; Fundamental research on materials; and Advanced functional materials. More than 5500 participants attended the congress, and the organizers received more than 700 technical papers. Based on the recommendations of symposium organizers and after peer reviewing, 490 papers have been included in the present proceedings, which showcase the latest original research results in the field of materials, achieved by more than 300 research groups at various universities and research institutes.
Analysis on the Major Environmental Factors Affecting the Weather Resistance of Polyester Coating -- Influence of Surface Buffer Layer Thickness and Deposition Rate on the Release Rate of Silver Ions in Ag-TiOx Nanocomposites -- Effect of Fiber Content on Surface Performance of Potassium Titanate Whiskers and Carbon Fiber-Reinforced Phenolic Composites.
Keywords: Surfaces (Technology).; Thin films; Manufactures; Mathematical physics; Coatings; Tribology; Corrosion and anti-corrosives.; Surfaces, Interfaces and Thin Film; Machines, Tools, Processes; Theoretical, Mathematical and Computational Physics; Coatings; Tribology; Corrosion